The effect of educational videos depicting the impact of smoking on young adults smokers: a qualitative study - Sutrisno, Resti Yulianti; Suryana, Baruna Hendri; Sutantri, Sutantri; Sugiyo, Dianita; Choliq, Idham; Aditjondro, Enrico; Jamaludin, Thandar Soe Sumaiyah; Wulandari, Bertha Tesma (Asian Pacific Organization for Cancer Prevention, 2024)
Objective: The morbidity caused by smoking is increasing. Meanwhile, very few people access smoking cessation counseling in primary health care. Therefore, more massive and innovative efforts to increase motivation to quit smoking are needed. This research aims to explore smokers’ perceptions of three types of videos that describe the impact of smoking.